Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.2 - Inverse Functions - Practice: 8

Answer

$f^{-1} (x) = x+6$

Work Step by Step

$f (x) = x-6$ Step 1: Replace $f (x)$ with $y$. $$y = x-6$$ Step 2: Interchange $x$ with $y$. $$x = y-6$$ Step 3: Solve for $y$. $$y = x+6$$ Step 4: Replace $y$ with $f^{-1} (x)$. $$f^{-1} (x) = x+6$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.